Self Efficacy, Occupational Characteristics and Work Environment Its Influence on Work Stress of Medical Workers during the Covid-19 Pandemic at Puskesmas in Sakra District, Lombok Timur, Nusa Tenggara Barat - Sulaimiah Sulaimiah; Zainal Abidin; Sarifudin Serif (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the significant negative effect of self-efficacy on work stress, job characteristics on work stress, and the significant negative effect of the work environment on work stress on the medical staff at the health centers in the Sakra sub-district, namely the West Sakra Public Health Center, the Public Health Center, Ringsing and Lepak Health Center, using a sample of 78 consisting of doctors, nurses, midwives and pharmacists. The type of research used is causal associative with questionnaire, interview and documentation techniques complete with data collection tools, questionnaires. The analytical tool used is multiple linear regression, where the variable X1 is self efficacy. X2 work characteristics, X3 Work environment with Y variable is work stress, which is equipped with t test, F test as a model test, determinant test,previously carried out the instrument test where all the tests carried out were met, both validity test, reliability test, classical assumption test, namely normality test, multicollinearity, and heteroscedasticity test. Meanwhile, multiple regression results found all independent variables (self efficacy, job characteristics, work environment) has a significant negative effect on the dependent variable (work stress).